Metode tafsir al-Qur’an: Tahlili dan Ijmali - Mawati, Tiarah (Maliki Interdisciplinary Journal, 2024)
As a book of Muslims, the Qur’an cannot be understood contextually. The Qur’an needs to be explored the purpose and purpose of the verse revealed by Allah. To explore and understand the hidden meaning in it, humans need a knowledge known as tafsir. Scholars have taken many interpretation methods that are used to explore the meaning of a verse of the Qur’an. Among the methods of interpretation are the tafsili and ijmali methods.